Novel Gerota-edge-sling technique facilitates retroperitoneal robot-assisted partial nephrectomy: a comparative study - Wei Chen; Qixiang Fang; Haomin Ren; Lei Ma; Jin Zeng; Shangshu Ding; Dapeng Wu (BMC Urology, 2022)
Abstract Background Retroperitoneal robotic partial nephrectomy is markedly restricted by limited space and visual field. We introduced a novel Gerota-edge-sling (GES) technique with self-designed traction devices to overcome these defects by attaching Gerota fascia to abdominal wall, and comparatively evaluated its utilization with routine technique. Methods A retrospective analysis was performed for consecutive patients who underwent routine (control group) or GES assisted (GES group) retroperitoneal robotic partial nephrectomy for localized renal tumors in our hospital between March 2018 and June 2020. Clinical data of perioperative outcomes and complications were collected and compared. Comparison of outcomes between anterior versus posterior tumor subgroups was also conducted. Linear regression analysis was used to define the relationship between dissection time and perinephric fat status in each group. Results Totally 103 patients were included, 48 in control and 55 in GES group respectively. All the procedures were completed successfully without conversion or positive surgical margin. GES group had significantly decreased console time (91 ± 36 min vs. 117 ± 41 min, p < 0.01) and dissection time (67 ± 35 min vs. 93 ± 38 min, p < 0.01) than control, while ischemia time, blood loss, and nephrometry score comparable between them. No major postoperative complications occurred. Dissection time of GES group was notably shorter than that of control in both anterior/posterior subgroups. Only in control group, dissection time was positively associated with perinephric fat status. Conclusions The GES technique acting as an adjunct to robotic arms with space-sparing feature, notably improves surgical exposure and facilitates dissection in retroperitoneal partial nephrectomy, while having great feasibility, efficacy and safety.